Incidence, presentation and outcome of kawasaki disease among children admitted to Hospital Raja Perempuan Zainab II - Wan Mohamad, Wan Md Hafizi (2023)
Introduction: Kawasaki disease (KD) is an acute febrile illness in early childhood characterized by fever for more than five days, accompanied by other symptoms such as a rash, conjunctiva inflammation, oral changes, lymphadenopathy, and extremity changes. KD is the leading cause of acquired heart disease in children. However, there are limited published studies on the disease in Malaysia. Thus, this study was conducted to determine the incidence of KD and its associated risk factors in late resolution of coronary artery dilatation in the Kelantan population. Methodology: This 12 years study involved 105 KD patients of Hospital Raja Perempuan Zainab II. Socio-demographic characteristics, clinical profile, biochemical evidence and echocardiography were recorded. Single and multiple logistic regression were used to determine the associated risk factors for late resolution of coronary dilatation. Result: Total of 105 patients were involved (59 were male, 46 were female). Most patients were Malay (96.2%) and the mean age was 28.2 months. Among those patients, 37.1% were complete KD and 62.9% incomplete KD. The hospital incidence of KD during the study period was 93 patients per 100,000 paediatric patients. The study found that almost all patients (99%) presented with a fever lasting more than five days, followed by rashes (80%). Majority of patients had high inflammatory markers. The study revealed that 34.6% of patients required more than 24 months for coronary artery dilatation to resolve. The only variable significantly associated with late resolution of coronary artery dilation was the number of coronary arteries involved (more than 1 vessel during presentation). Conclusion: This study showed the incidence of KD patient was still high in Kelantan. KD was highly associated with coronary artery abnormality. Involvement of more than 1 coronary artery during presentation was associated with the late resolution of coronary artery in 2 years of follow up.